PARTISIPASI TENAGA KERJA WANITA DI USAHA BUNGA POTONG DI KELURAHAN KAKASKASEN II, KECAMATAN TOMOHON UTARA, KOTA TOMOHON - Verro Stevanus Tampun Worung; Charles R. Ngangi; Ellen G. Tangkere (Sam Ratulangi University, 2016)
In this era of globalization, many efforts have done in order to earn money for the family. Efforts in agriculture be one choice of families and communities. In general, the development has opened up opportunities for women to engage in various businesses in the agricultural sector which has been dominated by men. The purpose of this study was to determine the participation of women owners or workers in the cut flower business in Kakaskasen II Village, North Tomohon sub district, Tomohon. The study lasted for 3 months, namely in November 2015 until January 2016, ranging from research preparation to the formulation of a research report. The data used in this study are primary and secondary data. Primary data was collected through direct interview to the respondents. Method of sample selection has used purposive sampling technique on nine women from 11 women as population who are owners or workers in the cut flower business. Data collection is a direct interview and observation (observation). Secondary data was collected from previous studies conducted by other researchers, but at the same location. Data analysis in this research using descriptive analysis and also using a Likert scale, with level 1 (underactive), 2 (active), 3 (highly active). This study found, based on an analysis using a Likert scale, that the number of female labor force participation index in the cut flower business (including planting, maintenance, cutting/ harvesting/buying, stringing, or sales) are at a point that 85.6% were categorized as high. Further analysis showed that the labor force participation rate of women in cut flower business with a score of up to 185 of the range of the number of ideal scoring the highest score was 216 and the lowest score was 72. Suggestions in this study, based on the conclusions derived, is the government should open up more opportunities to increase the number of business opportunities and work for women in cut flower business in order to alleviate the problem of female unemployment and poverty that exist in Tomohon City.*eprm*